Unimolecular Exciplexes by Ugi Four-Component Reaction - Ochs, Maria; Mayer, Bernhard; Müller, Thomas J. J. (Frontiers in Chemistry, 2019)
Exciplex or excited complex emission is an excited state process, arising from considerable charge transfer of an excited energy donor to an acceptor, which can be identified by the occurrence of a redshifted emission band that is absent in the individual constituents. Particularly interesting are exciplexes that are formed by intramolecular excited state interaction, which are inherently concentration independent. Based upon our previous experience in the Ugi-4CR syntheses of donor-acceptor conjugates capable of photoinduced intramolecular electron transfer (PIET), i.e. generation of light induced charge separation, we now disclose the diversity oriented approach on unimolecular exciplex emitters and their reference systems by Ugi-4CR. The photophysics is studied by absorption and emission spectroscopy and accompanied by DFT and TDDFT calculations.